Globalization Impacts on Socio-Economic Change: A Social Science Education Perspective in Indonesia - Siti Noviyanti; Tria Putri Agustin (Journal of Smart Pedagogy and Education, 2025)
This study examines how globalization-driven socio-economic shifts in 2024–2025 impact Social Science Education (IPS) in Indonesia. As the nation pursues "Golden Indonesia 2045," the acceleration of industrial downstreaming and the digital economy necessitates a globally competent citizenry. Utilizing a descriptive qualitative methodology and systematic review of 2020–2025 literature, this research explores the integration of global standards within the Kurikulum Merdeka. Findings reveal a polarized landscape where rapid digital growth coexists with an expanding informal labor market (59.40%) and a persistent digital divide. Despite progressive curriculum shifts toward "Deep Learning," implementation remains significantly hindered by systemic barriers, including teacher knowledge gaps and infrastructure disparities. Ultimately, IPS education must foster a socially critical and digitally literate population to bridge the urban-rural divide and ensure sustainable, inclusive national development.